Toward Sustainable Mars Exploration: A Perspective on Collaborative Intelligent Systems - Thomas Janssen; Ritesh Kumar Singh; Phil Reiter; Anuj Justus Rajappa; Priyesh Pappinisseri Puluckul; Mohmmadsadegh Mokhtari; Mohammad Hasan Rahmani; Erik Mannens; Jeroen Famaey; Maarten Weyn (Aerospace)
Mars has long captivated the human imagination as a potential destination for settlement and scientific exploration. After deploying individual rovers, the next step in our journey to Mars is the autonomous exploration of the Red Planet using a collaborative swarm of rovers, drones, and satellites. This concept paper envisions a sustainable Mars exploration scenario featuring energy-aware, collaborative, and autonomous vehicles, including rovers, drones, and satellites, operating around Mars. The proposed framework is designed to address key challenges in energy management, edge intelligence, communication, sensing, resource-aware task scheduling, and radiation hardening. This work not only identifies these critical areas of research but also proposes novel technological solutions drawn from terrestrial advancements to extend their application to extraterrestrial exploration.